The influence of perceived value to customer loyalty with customer satisfaction as an intervening variable on ESSE Brand Users in Manado - Umboh, Syallomika F. B. W.; Tulung, Joy E.; Wangke, Shinta J. C. (Yayasan Widyantara Nawasena Raharja, 2024)
In today's competitive business landscape, establishing and maintaining customer loyalty is crucial for the sustained success of brands. This study aims to shed light on how perceived value influences customer loyalty, and how customer satisfaction mediates this relationship. The study employs 100 respondents to gather comprehensive insights from ESSE Brand Users in Manado. The findings show that the perceived value is significant on customer satisfaction but not for customer loyalty while the customer satisfaction is significant on customer loyalty. By exploring the interplay between perceived value, customer satisfaction, and customer loyalty within the context of ESSE Brand Users in Manado, the study aims to provide valuable insights for marketing practitioners to enhance their strategies. Understanding how perceived value and customer satisfaction impact customer loyalty can help businesses tailor their offerings and customer service to build stronger brand loyalty among ESSE users in this specific market.